A Creative Approach To Learning For Students Of A Technical University - PhD Ganikhanova M. B; PhD, MBA Marina Kanushina (Peerian Journals Publishing, 2025)
In the modern educational system, learning English is essential for technical university students as it enhances their academic and professional opportunities. Traditional teaching methods often fail to engage students effectively, leading to passive learning. A creative approach to English language acquisition, incorporating innovative teaching strategies, digital tools, and real-life applications, can significantly improve student motivation and comprehension. This article explores various creative techniques, such as gamification, project-based learning, roleplaying, and the integration of technical content into language instruction, to enhance English proficiency among engineering and technical students
Keywords: engineering; improve; approach